EVALUATION OF THE EFFECTIVENESS OF HEALTH CARE INSTITUTIONS (INNOVATIVE ECONOMY, 2024)
Hurzhyi P.O. EVALUATION OF THE EFFECTIVENESS OF HEALTH CARE INSTITUTIONSPurpose. The aim of the article is to generalize the tools for evaluating the effectiveness of health care institutions and develop theoretical and methodological recommendations for their application in order to develop sound management decisions for their successful functioning.Methodology of research. The following methods were used in the research process: theoretical generalization, induction and deduction, abstraction – to determine the conceptual basis of the economic analysis of the activity of health care institutions and methodical approaches to evaluating the effectiveness of their functioning; generalization – for formulating definitions of medical, social and economic efficiency and conclusions based on research results.Findings. The essence of medical, social and economic efficiency is revealed and the indicators used to evaluate them are determined. The necessity of carrying out an economic analysis of the activity of health care institutions is substantiated and its conceptual principles are established (purpose, tasks, methods, types, sources of information and organizational stages of its implementation). Indicators of the effectiveness of the medical institution as a whole and by the used resources (labour, material, financial) were determined. Specific methods of analysis of alternative methods of action of a medical facility are presented (cost minimization method, “cost-effectiveness” method, “cost-benefit” method, “cost-utility” method).Originality. The theoretical and methodological aspects of evaluating the effectiveness of the health care institution have gained further development.Practical value. The system of indicators for evaluating the effectiveness of health care institutions, substantiated by the results of the research, can be used to develop directions for improving their functioning in the market of medical services.Key words: efficiency, evaluation, health care facility, material resources, labour resources, financial resources, economic analysis.
Keywords: efficiency; evaluation; health care facility; material resources; labour resources; financial resources; economic analysis.